2019
DOI: 10.1051/0004-6361/201833530
|View full text |Cite
|
Sign up to set email alerts
|

Multiply imaged time-varying sources behind galaxy clusters

Abstract: With upcoming (continuum) surveys of high-resolution radio telescopes, detection rates of fast radio bursts (FRBs) might approach 10 5 per sky per day by future extremely large observatories, such as the possible extension of the Square Kilometer Array (SKA) to a phase 2 array. Depending on the redshift distribution of FRBs and using the repeating FRB121102 as a model, we calculate a detection rate of multiply-imaged FRBs with their multiply-imaged hosts caused by the distribution of galaxy-cluster scale gravi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…I and II, the central peaks are not reconstructed very well but for one of the peaks, which had fewer images near it, the reconstruction is worse compared to the other peak. In general having more images is always beneficial, however, the presence of central images (maxima in the arrival time surface) does not always guarantee better constrained central regions (Wagner et al 2019). For a circularly symmetric lens the deflection angle is determined only by the total mass interior to a point, and the more central a point is, the less mass is enclosed by it.…”
Section: Reconstructed Mass Mapsmentioning
confidence: 99%
“…I and II, the central peaks are not reconstructed very well but for one of the peaks, which had fewer images near it, the reconstruction is worse compared to the other peak. In general having more images is always beneficial, however, the presence of central images (maxima in the arrival time surface) does not always guarantee better constrained central regions (Wagner et al 2019). For a circularly symmetric lens the deflection angle is determined only by the total mass interior to a point, and the more central a point is, the less mass is enclosed by it.…”
Section: Reconstructed Mass Mapsmentioning
confidence: 99%
“…Available cases are still rare, yet, multiply-imaged quasars or supernovae behind clusters may be detected more frequently with future surveys. As investigated in Wagner et al (2019), fast radio bursts could be equally likely found as multiple images in a galaxy cluster. Advantages in favour of employing cluster-scale lenses are the higher relative precision of the time delay measurements and the numerous constraints on the lens model coming from a multitude of multiple-image systems.…”
Section: Resultsmentioning
confidence: 97%
“…Time delays can provide very useful information about the overall lensing potential, and the time delay fitness measure proposed in Liesenborgs et al (2009) was evaluated more thoroughly. The test was similar to the one used in Liesenborgs & De Rijcke (2012); Wagner et al (2019), where a lens with an elliptical version of a Navarro-Frenk-White (NFW; Navarro et al (1996)) mass distribution was used to gauge the effect of the addition of time delay information to the images of only a single source. Here, it was found that when adding time delay information to the images of all sources, the old fitness measure can over-focus the images whereas a newly proposed expression appears to avoid this.…”
Section: Discussionmentioning
confidence: 99%